1993
DOI: 10.1177/105477389300200408
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fiber Nursing Intervention

Abstract: Constipation is a major complaint of older adults. Approximately 30% of older adults use laxatives at least once weekly, and laxatives account for 1% of physician prescriptions in addition to approximately 700 over-the-counter preparations. This study evaluated the efficacy of a fiber and fluid nursing intervention on the maintenance of bowel movements and elimination aid withdrawal in residents of a long-term health care facility. The findings indicated that the number of bowel movements reached a peak at 3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…To ensure that the desirable daily fluid intake is achieved to prevent constipation, 10 or more cups/glasses would need to be consumed, therefore this was scored 'zero'. A fluid intake of a minimum of 1.5 l/day was considered adequate for constipation prevention (Meza et al, 1984;Rodrigues-Fisher et al, 1993;Gibson et al, 1995;Armstrong-Esther et al, 1996;Ouellet et al, 1996;Duffy and Zernike, 1997) and would measure at 6 cups/glasses per day (Wilson, 1999). The sub-category of '6-9 cups/glasses consumed daily' was then included, which was scored as 'one'.…”
Section: Fluid Intakementioning
confidence: 99%
“…To ensure that the desirable daily fluid intake is achieved to prevent constipation, 10 or more cups/glasses would need to be consumed, therefore this was scored 'zero'. A fluid intake of a minimum of 1.5 l/day was considered adequate for constipation prevention (Meza et al, 1984;Rodrigues-Fisher et al, 1993;Gibson et al, 1995;Armstrong-Esther et al, 1996;Ouellet et al, 1996;Duffy and Zernike, 1997) and would measure at 6 cups/glasses per day (Wilson, 1999). The sub-category of '6-9 cups/glasses consumed daily' was then included, which was scored as 'one'.…”
Section: Fluid Intakementioning
confidence: 99%
“…Research examining risk factors in an elderly population (n = 36) concluded that fibre and fluid intake was not significantly different in constipated versus non-constipated individuals (Towers et al, 1994). Values provided for fluid intake in the two groups indicate that ''3.4 glasses (8 oz) of fluid'' were consumed on average daily, which is lower than the recommended minimum fluid intake (Alford, 1991;Rodrigues-Fisher et al, 1993;Gibson et al, 1995). Values provided for fluid intake in the two groups indicate that ''3.4 glasses (8 oz) of fluid'' were consumed on average daily, which is lower than the recommended minimum fluid intake (Alford, 1991;Rodrigues-Fisher et al, 1993;Gibson et al, 1995).…”
Section: Role Of Fluid Intakementioning
confidence: 92%
“…This rationale has been proved by many research studies which have reported increased colonic activity with a diet high in fibre, measured by transit times of food through the gut (Burkitt et al, 1972;Harvey et al, 1973;Burkitt et al, 1974;Cummings et al, 1978;Graham et al, 1982;Kelsay and Clark, 1984;Preston and Lennard-Jones, 1985;Davies et al, 1986;Muller-Lissner, 1988;Rodrigues-Fisher et al, 1993;Cheskin et al, 1995;Cameron et al, 1996;Voderholzer et al, 1997). This rationale has been proved by many research studies which have reported increased colonic activity with a diet high in fibre, measured by transit times of food through the gut (Burkitt et al, 1972;Harvey et al, 1973;Burkitt et al, 1974;Cummings et al, 1978;Graham et al, 1982;Kelsay and Clark, 1984;Preston and Lennard-Jones, 1985;Davies et al, 1986;Muller-Lissner, 1988;Rodrigues-Fisher et al, 1993;Cheskin et al, 1995;Cameron et al, 1996;Voderholzer et al, 1997).…”
Section: Role Of Dietary Fibrementioning
confidence: 96%
See 2 more Smart Citations